Strengthening Craft-Based MSME Competitiveness Through an Empowerment Model in Mojokerto’s Creative Incubation Program - Ananta, Ayu Nevilia; Harmawan, Bagus Nuari (UIR Press, 2026)
The development of the creative economy has positioned entrepreneurship incubation programs as a strategic approach to strengthen craft-based micro and small enterprises. This study aims to answer how the community empowerment process unfolds within the Creative Craft Design Entrepreneurship Incubation Program under the 5 Creative Subsector Scheme in Mojokerto City. Using Wilson’s empowerment framework awakening, understanding, harnessing, and using, the research investigates the extent to which the program contributes to the advancement of fashion-related craft enterprises. A qualitative case study approach was employed, and data were collected through observation, semi-structured interviews, and documentation involving program participants and the implementing agency. The findings show that the program substantially enhanced participants’ technical, managerial, relational, and psychological capacities. In the awakening stage, participants developed greater awareness of their entrepreneurial potential, though motivation levels varied. The understanding stage revealed notable improvements in design quality, production techniques, business management, and digital marketing skills. During the harnessing stage, several participants effectively utilized program facilities, networks, and acquired knowledge, while others exhibited continued dependency on the implementing agency. The using stage demonstrated emerging business independence, marked by increased sales, improved operational management, and more consistent marketing practices, although some participants progressed slowly due to limited commitment. Overall, the program contributes meaningfully to the gradual empowerment and professionalization of craft-based enterprises. These findings highlight the importance of continuous mentoring, digital capacity building, and tailored support to strengthen the sustainability and competitiveness of creative industry entrepreneurs.